Perinatal Data Collection: Current Practice in the Australian Nursing and Midwifery Healthcare Context. Issue 1 (March 2013) - Craswell, Alison; Moxham, Lorna; Broadbent, Marc
The collection of perinatal data within Queensland, Australia, has traditionally been achieved via a paper form completed by midwives after each birth. Recently, with an increase in the use of e-health systems in healthcare, perinatal data collection has migrated to an online system. It is suggested that this move from paper to an e-health platform has resulted in improvement to error rates, completion levels, timeliness of data transfer from healthcare institutions to the perinatal data collection and subsequent publication of data items. Worldwide, perinatal data are collected utilising a variety of methods, but essentially data are used for similar purposes: to monitor outcome patterns within obstetrics and midwifery. This paper discusses current practice in relation to perinatal data collection worldwide and within Australia, with a specific focus on Queensland, highlights relevant issues for midwives, and points to the need for further research into the efficient use of an e-health platform for perinatal data collection.